2019
DOI: 10.1111/jcmm.14430
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from tendon stem cells promote injury tendon healing through balancing synthesis and degradation of the tendon extracellular matrix

Abstract: Tendon injuries are common musculoskeletal system disorders in clinical, but the regeneration ability of tendon is limited. Tendon stem cells (TSCs) have shown promising effect on tissue engineering and been used for the treatment of tendon injury. Exosomes that serve as genetic information carriers have been implicated in many diseases and physiological processes, but effect of exosomes from TSCs on tendon injury repair is unclear. The aim of this study is to make clear that the effect of exosomes from TSCs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
160
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(160 citation statements)
references
References 40 publications
0
160
0
Order By: Relevance
“…Here we report that small EVs released by healthy human tendon fibroblasts also contained a significantly high abundance of TGFβ1 compared to MyoX and FibX. A recent study showed that injection of exosomes isolated from cultures of tendon progenitors into an in vivo collagenase-induced tendinopathy model in rat Achilles increased type I collagen synthesis and improved tissue biomechanics [ 16 ]. Another study showed that the ability of tendon exosomes to reprogram mesenchymal stem cells to produce type I collagen could be blocked using a TGFβ inhibitor [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we report that small EVs released by healthy human tendon fibroblasts also contained a significantly high abundance of TGFβ1 compared to MyoX and FibX. A recent study showed that injection of exosomes isolated from cultures of tendon progenitors into an in vivo collagenase-induced tendinopathy model in rat Achilles increased type I collagen synthesis and improved tissue biomechanics [ 16 ]. Another study showed that the ability of tendon exosomes to reprogram mesenchymal stem cells to produce type I collagen could be blocked using a TGFβ inhibitor [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of tenocytes in a number of in vitro and in vivo experimental models with EVs from various sources, e.g. plasma [ 14 ], adipose stem cells [ 15 ], tendon progenitors [ 16 ], macrophages [ 17 ], have demonstrated that signalling through EVs can modulate the expression of genes that regulate ECM synthesis and remodelling. Exosomes derived from tendon cells have also been reported [ 18 , 19 ]; and one study showed that tendon cell-derived exosomes induce the expression of tenogenic genes in bone marrow-derived mesenchymal stem cells in a TGFβ-dependent manner [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…in EVs are crucial in increasing cell migration and activating pro-MMP2, as well as in the degradation of ECM-proteins [25]. We were further interested to analyze MMP3, which seems to be crucial in connective-tissue remodeling and has been found in adipocyte-derived EVs [26].…”
Section: Plos Onementioning
confidence: 99%
“…We were further interested to analyze MMP3, which seems to be crucial in connective-tissue remodeling and has been found in adipocyte-derived EVs [26]. Furthermore, Wang et al have been shown that EV derived from tendon stem cells, injected on rat tendon injury model significantly decreased MMP3 expression and increased the expression of Collagen type I promoting tendon healing [27,25]. However, our WB analysis showed the complete absence of MMP3 in rBMSCs-EVs, despite its confirmed presence in the originating rBMSCs (Fig 3C).…”
Section: Plos Onementioning
confidence: 99%
“…We performed the isolation and identification of rat TSCs as our previously studies. 12,16 Briefly, rats in all groups were euthanized, and then, Achilles tendons were carefully collected. The samples were Isolated cells were cultured under conditions of 37°C with 5% CO 2 for 2 days, then washed in PBS to discard non-adherent cells.…”
Section: Isolation and Identification Of Rat Tscsmentioning
confidence: 99%